An Analysis of Deixis Found in Student English Textbook When English Rings a Bell for the Eight Grade of Junior High School - Purba, Fanny Ramayani; Sidabutar, Usman; Silitonga , Harpen (Journal of Education and Teaching Learning, 2024)
The aims of this research were to determine the the type deixis and the most dominating type of deixis found in students' English Textbook  For The Eight Grade of Junior High School. The design of this study is descriptive qualitative method. The source of data of this study was the conversations contained deixis found in students' English Textbook "When English Rings A Bell" For The Eight Grade of Junior High School. The technique of collecting data used by the resercher was observation with technique of taking note techniques. The data was analyzed By applying  the  theory  of  creswell  (2007) and to  classifying  the  types  of deixis  use  the  theory  of Yule  (1996).  The results show that there were three types of deixis found in students' English Textbook "When English Rings A Bell" for the eight grade of Junior High School, namely person deixis, spatial deixis, and temporal deixis. There were a total of 472 deixis data that contained deixis. Among them there were person deixis was 389 data and has a percentage of 82,41%, spatial deixis was  37 data and has a percentage of 7,84% and temporal deixis was 46 data and has a percentage of  9,75%.